The effectiveness of a twice-daily skin-moisturising regimen for reducing the incidence of skin tears - Carville, Keryln; Leslie, Gavin; Osseiran-Moisson, Rebecca; Newall, Nelly; Lewin, Gill (Wiley-Blackwell Publishing Ltd, 2014)
A cluster randomised controlled trial was conducted to evaluate the effectiveness of a twice-daily moisturising regimen as compared to ‘usual’ skin care for reducing skin tear incidence. Aged care residents from 14 Western Australian facilities (980 beds) were invited to participate. The facilities were sorted into pairs and matched in terms of bed numbers and whether they provided high or low care. One facility from each matched pair was randomised to the intervention group. Consenting residents in an intervention facility received a twice-daily application of a commercially available, standardised pH neutral, perfume-free moisturiser on their extremities. Residents in the control facilities received ad hoc or no standardised skin-moisturising regimen. Participant numbers were sufficient to detect a 5% difference in incidence rate between the two groups with 80% power and a significance level of P=0·05, and the inter-cluster correlation coefficient was 0·034. Data were collected over 6 months. A total of 1396 skin tears on 424 residents were recorded during the study. In the intervention group, the average monthly incidence rate was 5·76 per 1000 occupied bed days as compared to 10·57 in the control group. The application of moisturiser twice daily reduced the incidence of skin tears by almost 50% in residents living in aged care facilities.